2021
DOI: 10.1186/s12978-021-01077-z
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence against adolescents and young women in sub-Saharan Africa: who is most vulnerable?

Abstract: Background Intimate partner violence (IPV) is a global public health and human rights issue that affects millions of women and girls. While disaggregated national statistics are crucial to assess inequalities, little evidence exists on inequalities in exposure to violence against adolescents and young women (AYW). The aim of this study was to determine inequalities in physical or sexual IPV against AYW and beliefs about gender based violence (GBV) in sub-Saharan Africa (SSA). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
41
7

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 31 publications
8
41
7
Order By: Relevance
“…No statistical significance was found for women with 3 or more children and IPV. Acceptance of IPV by women was consistently shown to be associated with higher IPV reporting [ 9 , 13 ], and this was also borne out of this study. Alcohol use by one’s husband/partner was consistently associated with increased IPV experience by women [ 6 , 8 , 13 ], and this study reinforces this association.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…No statistical significance was found for women with 3 or more children and IPV. Acceptance of IPV by women was consistently shown to be associated with higher IPV reporting [ 9 , 13 ], and this was also borne out of this study. Alcohol use by one’s husband/partner was consistently associated with increased IPV experience by women [ 6 , 8 , 13 ], and this study reinforces this association.…”
Section: Discussionsupporting
confidence: 70%
“…Based on previous studies [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ], 10 variables at the individual, husband/partner, and familial levels were studied for association with respondents having ever experienced intimate partner violence, i.e., women’s age, women’s educational attainment, women’s occupation, wealth index of the household/family, residential status in terms of urban and rural, number of living children, participation in decision making, acceptance of IPV, husband/partner’s use of alcohol, and having witnessed one’s father physically beating up one’s mother. Details on the derivation of each explanatory variable is provided as under:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…• The paper by Melesse et al extends this point to within country inequalities, underscoring that disparities in age of sexual debut, early marriage, and early childbearing are persisting and growing across a number of countries [9]. • The paper by Wado et al notes that while all groups of adolescent girls/young women (and adult women for that matter) are affected by intimate partner violence, those who are from poor families, have limited education and live in rural areas are most affected [10]. • The paper by Cane et al highlights the disparities in the levels and trends of HIV prevalence between girls/young women and boys/young men, and between rural and urban residents, while also pointing to the considerable progress that has been made in reducing HIV transmission in all groups [11].…”
Section: Introductionmentioning
confidence: 99%
“…A study with 930 pregnant black-skinned and Latino adolescents found that 38% experienced TDV in the last trimester of pregnancy ( 8 ) . A study conducted in 27 countries in sub-Saharan Africa found that a median of 25.2% of adolescents and young women reported TDV, reaching 43.3% in some countries ( 9 ) .…”
Section: Introductionmentioning
confidence: 99%